2014
DOI: 10.1007/s11094-014-1111-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Cytostatic Activity of some Pregna-D′-Pentaranes on HeLa Cell Culture

Abstract: The effects of nine new pregnane steroids containing substituents in the 16a,17a-and/or 3-, 6-, and 19-positions of the steroid framework on the viability of HeLa cervical cancer cells were studied. It was shown that the 6-oximes of 3-keto-and 3-hydroxy-4-dehydrosteroids with a 16a,17a-cyclohexane substituent and 3-keto-4-dehydrosteroids with a 16a,17a-phenylcyclopropane substituent reduced the viability of the cell culture. Compound K1047 had the highest cytostatic effect and was promising as a potential horm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Progesterone inhibits TRPM7 expression, thereby switching acidotoxic necrosis of tumor cells to apoptosis [ 66 ]. A number of studies on HeLa cells have demonstrated the cytotoxic effect not only of progesterone, but also of its synthetic derivatives, the cytotoxic effect being observed both upon stimulation with estradiol and without stimulation [ 67 , 68 ].…”
Section: Clinical Use Of Gestagensmentioning
confidence: 99%
“…Progesterone inhibits TRPM7 expression, thereby switching acidotoxic necrosis of tumor cells to apoptosis [ 66 ]. A number of studies on HeLa cells have demonstrated the cytotoxic effect not only of progesterone, but also of its synthetic derivatives, the cytotoxic effect being observed both upon stimulation with estradiol and without stimulation [ 67 , 68 ].…”
Section: Clinical Use Of Gestagensmentioning
confidence: 99%